2000
DOI: 10.2337/diacare.23.6.861
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-induced hypoglycemia induces a rise in C-reactive protein.

Abstract: Sane , Saito H: Endogenous glucose production and glucose effectiveness in type 2 diabetic subjects derived from stablelabeled minimal model approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…Several studies have reported that hypoglycaemia increases the levels of a variety of inflammatory cytokines [9,10]. These in turn cause endothelial dysfunction, resulting in increased risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that hypoglycaemia increases the levels of a variety of inflammatory cytokines [9,10]. These in turn cause endothelial dysfunction, resulting in increased risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Strict glycaemia control using intensive insulin therapy increases the risk of hypoglycaemia. While it is well known that hypoglycaemia affects cognition, mood and consciousness, it also has profound effects on blood constituents [7,8], inflammatory cytokine level [9,10], and coagulation and fibrinolysis factors [11,12], mainly through the sympathoadrenal response to hypoglycaemia. These data suggest that hypoglycaemia induced by insulin injection may be implicated in the progression of atherosclerosis; however, there are no convincing in vivo data in support of this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Galloway et al [101] have reported a significant increase in CRP at 24 h after acute insulin-induced hypoglycaemia, both in subjects with type 1 diabetes (0.77-2.31 mg/L) and in healthy volunteers (0.32-0.96 mg/L). While it is unclear as to the role of CRP in the causation of atherogenesis, increasing evidence has implicated its involvement in acute vascular events, with data in vitro and in vivo demonstrating its possible pathogenetic qualities, and additionally CRP levels are predictive of outcome following cardiovascular events [102,103].…”
Section: Inflammation and Endothelial Dysfunctionmentioning
confidence: 99%
“…Hypoglycaemia induces sympatho-adrenal stimulation with potentially adverse cardiovascular consequences, 22 including QT interval prolongation, 23 and release of inflammatory cytokines that have an adverse impact on endothelial function. 24 These effects may trigger arrhythmias and exacerbate ischaemia, and this has been proposed as an explanation for the increased mortality seen with tightly controlled diabetes in the ACCORD study. 25 However, hypoglycaemia was reported in only 4.1% of patients in TITAN-ACS, and for the majority it was a single episode, this rate is lower than that in the other published randomised controlled trials (Table 4).…”
Section: Discussionmentioning
confidence: 99%